2023
DOI: 10.3390/ijms24119446
|View full text |Cite
|
Sign up to set email alerts
|

After Ischemic Stroke, Minocycline Promotes a Protective Response in Neurons via the RNA-Binding Protein HuR, with a Positive Impact on Motor Performance

Abstract: Ischemic stroke is the most common cause of adult disability and one of the leading causes of death worldwide, with a serious socio-economic impact. In the present work, we used a new thromboembolic model, recently developed in our lab, to induce focal cerebral ischemic (FCI) stroke in rats without reperfusion. We analyzed selected proteins implicated in the inflammatory response (such as the RNA-binding protein HuR, TNFα, and HSP70) via immunohistochemistry and western blotting techniques. The main goal of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 112 publications
(160 reference statements)
0
2
0
Order By: Relevance
“…These previous data in Supplemental Material demonstrate that targeting the vasculature can lead to improved stroke outcomes. 74,77,78 BI-0115 is a selective LOX-1 inhibitor that prevents the binding of the LOX-1 receptor and therefore inhibits the signaling cascade and possibly the upregulation of MMP-9. In comparison, JNJ0966 is a direct MMP-9 inhibitor that prevents the activation of MMP-9 by binding allosterically to the protease.…”
Section: Discussionmentioning
confidence: 99%
“…These previous data in Supplemental Material demonstrate that targeting the vasculature can lead to improved stroke outcomes. 74,77,78 BI-0115 is a selective LOX-1 inhibitor that prevents the binding of the LOX-1 receptor and therefore inhibits the signaling cascade and possibly the upregulation of MMP-9. In comparison, JNJ0966 is a direct MMP-9 inhibitor that prevents the activation of MMP-9 by binding allosterically to the protease.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is one of the leading causes of death worldwide and the most common cause of disability among adults, having a serious impact on the patient and family, but also upon the social and economic life [ 15 ]. The average cost of ischemic stroke per person, which includes inpatient care, rehabilitation, and aftercare, is estimated at 140 048 dollars in the United States [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its neuroprotective effects within the central nervous system (CNS) are facilitated by the blood-brain barrier (BBB). Research findings have indicated that MINO possess a safeguarding influence on central nervous system (CNS) disorders, namely depression [ 7 ], ischemic stroke [ 8 ], AD [ 9 ], and PD [ 10 ]. Thus far, evidence has demonstrated that MINO mitigates cognitive dysfunction by diminishing inflammation and apoptosis [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%